An investigation into human relation practices in the education sector in Kumasi. - Braso Amoah, Sandra (2015)
A thesis submitted to the Graduate School of Business KNUST, Kumasi, in partial fulfillment of the requirements for the award of a degree in Masters of Business Administration (HUMAN RESOURCE MANAGEMENT).